IOT futuristic integration with ERP systems: A review - Arjun Reddy Kunduru (International Journal on Human-Computing Studies, 2022)
The Internet of Things (IoT) and Enterprise Resource Planning (ERP) are two of the most disruptive information technologies, changing how modern enterprises operate. IoT enables connecting physical objects like machines, assets, and goods embedded with sensors, software, and connectivity to collect and exchange data over the internet. ERP software integrates business processes across departments into unified systems for insight and automation. Integrating IoT with ERP is an enormous opportunity for digital transformation across functions like manufacturing, logistics, and asset management. This research article provides a comprehensive analysis of the current status, key drivers, future potential, challenges, emerging approaches, and best practices related to IoT-ERP integration. While early use cases involve the basic connectivity of IoT with ERP for real-time visibility and reporting, huge potential exists for transformative changes through tighter convergence, like autonomous operations, intelligent workflows, new business models, etc. However, organizations face significant technology and business challenges around connectivity, data, security, integration complexity, skill shortages, and change management. The article discusses strategies to overcome these multifaceted challenges. Various integration approaches are emerging, leveraging specialized middleware, ERP vendor IoT platforms, partner ecosystems, integration platforms as a service, APIs, and microservices. Enterprises need to assess their landscape and priorities to pick optimal techniques. Adopting best practices around case-driven pilots, flexible integration architecture, cross-functional teams, and industry benchmarks can maximize benefits while minimizing risks. With aging legacy ERP and exponential IoT growth, integrating the two technologies is urgent for future success. When systematically implemented, integrated IoT and ERP will form the core digital platforms, enabling smarter, more efficient, and more innovative future enterprises.